Definition of major bleeding in clinical investigations of antihemostatic medicinal products in surgical patients - SCHULMAN, S.; ANGERÅS, U.; BERGQVIST, D.; ERIKSSON, B.; LASSEN, M. R.; FISHER, W. (Journal of thrombosis and haemostasis, 2010)
The definition of major bleeding varies between studies on surgical patients, particularly regarding the criteria for surgical wound‐related bleeding. This diversity contributes to the difficulties in comparing data between trials. The Scientific and Standardization Committee (SSC), through its subcommittee on Control of Anticoagulation, of the International Society on Thrombosis and Haemostasis has previously published a recommendation for a harmonized definition of major bleeding in non‐surgical studies. That definition has been adopted by the European Medicines Agency and is currently used in several non‐surgical trials. A preliminary proposal for a parallel definition for surgical studies was presented at the 54th Annual Meeting of the SSC in Vienna, July 2008. Based on those discussions and further consultations with European and North American surgeons with experience from clinical trials a definition has been developed that should be applicable to all agents that interfere with hemostasis. The definition and the text that follows have been reviewed and approved by relevant co‐chairs of the subcommittee and by the Executive Committee of the SSC. The intention is to seek approval of this definition from the regulatory authorities to enhance its incorporation into future clinical trial protocols.